2016
DOI: 10.1002/jmri.25351
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical shift-encoded water-fat MRI and MR spectroscopy in quantification of marrow fat in postmenopausal females

Abstract: Purpose To validate a chemical shift‐encoded (CSE) water–fat imaging for quantifying marrow fat fraction (FF), using proton magnetic resonance spectroscopy (MRS) as reference. Materials and Methods Multiecho T2‐corrected MRS and CSE imaging with eight‐echo gradient‐echo acquisitions at 3T were performed to calculate marrow FF in 83 subjects, including 41 with normal bone mineral density (BMD), 26 with osteopenia, and 16 with osteoporosis (based on DXA). Eight participants were scanned three times with repositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 40 publications
(116 reference statements)
7
40
2
Order By: Relevance
“…So far, few validation studies have compared MRI‐based PDFF to MRS‐based estimations of bone marrow fat content in vivo. These earlier data suggested good agreement between imaging‐determined and MRS‐based PDFF, with a small reported mean bias of up to ±2.2% and coefficients of determination ( r 2 ) ranging from 0.87–0.96, demonstrating high accuracy of chemical shift‐encoding based MRI in characterizing bone marrow PDFF . In line with these findings, PDFF obtained with six‐echo multipoint Dixon sequences also showed high linearity and small bias against MRS among the three MR imagers in our study ( r 2 , 0.888–0.921).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…So far, few validation studies have compared MRI‐based PDFF to MRS‐based estimations of bone marrow fat content in vivo. These earlier data suggested good agreement between imaging‐determined and MRS‐based PDFF, with a small reported mean bias of up to ±2.2% and coefficients of determination ( r 2 ) ranging from 0.87–0.96, demonstrating high accuracy of chemical shift‐encoding based MRI in characterizing bone marrow PDFF . In line with these findings, PDFF obtained with six‐echo multipoint Dixon sequences also showed high linearity and small bias against MRS among the three MR imagers in our study ( r 2 , 0.888–0.921).…”
Section: Discussionsupporting
confidence: 88%
“…In line with these findings, PDFF obtained with six‐echo multipoint Dixon sequences also showed high linearity and small bias against MRS among the three MR imagers in our study ( r 2 , 0.888–0.921). However, there was a slight overestimation of imaging‐based PDFF in comparison with MRS, as indicated by an intercept of –6.25 and a mean bias of –0.6% for pooled imaging data, which corroborates prior reports on vertebral bone marrow PDFF . We found that MRI‐determined PDFF measurements demonstrated higher linear correlation (ie, less variation) among the three MR imagers ( r 2 , 0.972–0.978) compared with those obtained between MRI‐determined PDFF and MRS.…”
Section: Discussionsupporting
confidence: 87%
“…A dual T 2 * correction can improve accuracy in fat fraction estimation, but it reduces the precision in fat quantification . Therefore, approaches with a single T 2 * correction or with a T 2 ′ correction (where T 2 ′ denotes the reversible spin dephasing relaxation constant) with a priori known water T 2 have been used. A dual T 2 * correction might be not severely affected by noise effects, when the fat quantification is performed not on a voxel‐by‐voxel basis but on a region of interest (ROI) level .…”
Section: Technical Aspects Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 99%
“…A study evaluating the reproducibility of signal intensity index (SII) measurements in healthy volunteers with MRI systems from different vendors and with different field strengths found intra-and inter-observer correlation coefficients ranging from 0.82 to 0.98 (102). In osteoporosis, the few studies performed until now have primarily assessed the bone marrow (103)(104)(105). Diffusionweighted imaging measures the Brownian motion of water at a microscopic level and provides information on cellularity and cellular integrity expressed in the apparent diffusion coefficient (ADC) (101).…”
Section: Mrimentioning
confidence: 99%